Can community monitoring improve the accountability of public officials? - Afridi, Farzana (2008)
This article discusses the nature and characteristics of monitoring the National Rural Employment Guarantee Scheme's implementation with a focus on the community control mechanisms existing in the two pioneering states of Rajasthan and Andhra Pradesh. These two states represent two relatively diverse models. Elements of both models need to be incorporated in order to make the process of community control of public programmes effective and sustainable. - Reproduced.
Keywords: Accountability; Civil service